Between Commitment and Image: Greenwashing Practices in Indonesia's Palm Oil Industry - Ahmar, Nurmala; Astuti, Tri; Darminto, Dwi Prastowo; Sekar, Calya; Asyraf , Muhammad (Journal Research of Social Science, Economics, and Management, 2025)
This article examines the practice of greenwashing in the sustainability reports of three major palm oil companies in Southeast Asia: PT A, PT B, and PT C. Employing the Critical Discourse Analysis (CDA) approach developed by Fairclough, this study analyzes the 2024 sustainability reports of these companies to identify the diction, discursive structures, and ideologies reproduced through corporate narratives. The findings reveal notable similarities in the use of symbolic language such as “zero deforestation,” “100% traceability,” and “net zero emission”, which are presented without methodological transparency or the inclusion of counter-narratives from civil society. Each of these companies constructs sustainability discourse as a tool for reputation and legitimacy rather than as a genuine instrument for ecological and social transformation. This article recommends a reformulation of sustainability reporting to be more reflective and accountable, incorporating risk disclosure, third-party audits, and the voices of affected communities.